Systemic lupus erythematosus with Guillian–Barre syndrome: A case report and literature review. Issue 25 (June 2018) - Gao, Zhaoli; Li, Xianhua; Peng, Tao; Hu, Zhao; Liu, Jie; Zhen, Junhui; Gao, Yanxia
Abstract: Introduction: We report a case of systemic lupus erythematosus (SLE) with Guillian–Barre syndrome (GBS) as the first symptom. Case presentation: A 30-year-old Chinese female with numbness and inductance of lower extremities 2 months previously. The electromyographic and cerebrospinal fluid findings supported inflammatory demyelinating disease, and the renal biopsy findings and rheumatoid-related results considered systemic lupus erythematosus. The patient received treatment with glucocorticoids and cyclophosphamide. Two months after the treatment, the patient's limb numbness and weakness disappeared, and the urinary protein was decreased significantly. Conclusions: Our case highlights the importance of the early diagnosis and treatment of SLE. Systemic lupus erythematosus is a multifactorial participant autoimmune systemic disease for which the clinical manifestations are complex and diverse. Glucocorticoid and cytotoxic drugs can be used in clinical treatment. If the disease is not diagnosed early, it could also delay treatment. Patients who receive an early diagnosis and appropriate treatment may have a better prognosis. Data Sources: Data were collected from the patient's electronic medical records and the hospital laboratory medicine database.